Burnout as Mediateer of The Influence of Organizational Support and Family Support on Job Stress at KSPPS Tunas Artha Mandiri - Ketut Bayu Tresna Prasetya; Budi Eko Soetjipto; Sopiah (Economics and Business Journal (ECBIS), 2023)
The purpose of this study is to investigate the effects of organizational and family support on work stress among female employees at KSPPS Tunas Artha Mandiri, as well as to examine the role of burnout as a mediator between these variables. The study aims to provide a better understanding of the factors that influence work stress among female workers, in order to provide recommendations for improving employee well-being and company productivity. The population of the study consists of 641 female employees in the company. The method used is a quantitative approach and path analysis. The results show that organizational support has a negative and significant effect on burnout, while family support has a positive and significant effect on burnout. Both organizational and family support have a negative and significant effect on work stress. Burnout has a positive and significant effect on work stress but does not mediate the effects of organizational and family support on work stress